Factors associated with the presence of multiple Lugol-voiding lesions in patients with esophageal squamous-cell carcinoma. Issue 5 (1st July 2014) - Katada, C.; Muto, M.; Tanabe, S.; Higuchi, K.; Sasaki, T.; Azuma, M.; Ishido, K.; Katada, N.; Sakuramoto, S.; Yamashita, K.; Masaki, T.; Nakayama, M.; et al.
Summary: Multicentric squamous dysplasia of the esophagus is characterized by multiple L ugol-voiding lesions (LVLs ) on L ugol chromoendoscopy. Multiple LVLs are associated with a very high risk of multiple cancers arising in the esophagus as well as the head and neck. To gain insight into the pathogenesis of multiple LVLs of the esophageal mucosa, we studied risk factors for the development of such lesions in 76 patients who had a current or previous diagnosis of esophageal squamous cell carcinoma. All patients underwent L ugol chromoendoscopy of the esophageal mucosa. The history of tobacco and alcohol use was documented. Polymorphisms of the aldehyde dehydrogenase type 2 (ALDH2 ) gene were identified by polymerase chain reaction using sequence-specific primers. Clinical factors related to multiple LVLs were analyzed. All patients with multiple LVLs were drinkers. On univariate analysis, male sex (odds ratio [OR ] 15, 95% confidence interval [CI ] 1.84–122.45: P = 0.011), presence of the ALDH2-2 allele (OR 4.5, 95% CI 1.55–13.24: P = 0.006), and smoking index ≥1000 (OR 2.6, 95% CI 1.02–6.6: P = 0.045) were associated with multiple LVLs . On multivariate analysis, male sex (OR 10.02, 95% CI 1.13–88.44: P = 0.038) and presence of the ALDH2-2 allele (OR 4.56, 95% CI 1.4–14.82: P = 0.012) were associated with multiple LVLs . Among drinkers, a daily alcohol intake of ≥100 g pure ethanol with the ALDH2-2 allele (OR 17.5, 95% CI 1.97–155.59: P = 0.01) and a daily alcohol intake of <100 g pure ethanol with the ALDH2-2 allele (OR 8.85, 95% CI 1.68–46.69: P = 0.01) more strongly correlated with multiple LVLs than did a daily alcohol intake of <100 g pure ethanol without the ALDH2-2 allele, whereas a daily alcohol intake of ≥100 g pure ethanol without the ALDH2-2 allele (OR 4.0, 95% CI 0.54–29.81: P = 0.18) did not. In conclusion, male sex and the ALDH2-2 allele are associated with an increased risk for multiple LVLs of the esophageal mucosa in patients with esophageal squamous cell carcinoma. Among drinkers with the ALDH2-2 allele, the risk of multiple LVLs increased in parallel to the daily alcohol intake.